Optimization of serious bacterial infections intensive therapy in children in Anesthesiology and Intensive Care Department - M. Yu. Kurochkin; A. H. Davydova; Yu. V. Horodkova (Zaporožskij Medicinskij Žurnal)
Effective selection of antibiotics in children with severe bacterial infections is often difficult because of microflora resistance. Extracorporeal detoxication methods, particularly discrete plasmapheresis are usually used for septic shock and total organ failure prevention.